Effect of the European Court of Human Rights case-law on judgments of Polish courts in the crime of hate speech - Dorota Habrat (Juridical Tribune, 2019)
The Convention on the Protection of Human Rights and Fundamental Freedoms and judgments of the European Court of Human Rights set the basic direction of judicial practice in Poland by introducing elementary principles of human rights observance by public authorities. The aim of the study was to analyze the impact of selected judgments of the European Court of Human Rights on the judicature of courts in Poland regarding the limits of freedom of expression in the context of the hate crime. The basic standards and the level of freedom of expression in Polish law, as well as judicial practice in this respect, have been defined. The analysis of standards has been limited to the aspect of the limits of freedom of speech in the context of hate speech. The scope of protection of statements in Polish law is, in principle, consistent with the ECHR jurisprudence. It follows that it is generally acceptable to extend the scope of penalization of statements containing incitement to hatred and violence of a racist or xenophobic nature, in particular, if they take the form of public insults, slander or threats. The jurisprudence of Polish courts is increasingly in line with international standards.